ANALISIS KEMAMPUAN KOMUNIKAI MATEMATIS PESERTA DIDIK KELAS VII SMP NEGERI 1 PADANG TAHUN AJARAN 2019/2020 - Gusti Nadya Varenska (Departemen Matematika, 2020)
Mathematical communication skills are very important in learning mathematics in schools.It is one of the abilities which every student must have and also a tool which can be used to solve problems, especially with math problems. The purpose of this study is to describe the students’ mathematical communication skills in solving math problems in the high, middle, and low ability range, which are from class VII SMP Negeri 1 Padang in the 2019/2020 academic year.Keywords—Mathematical communication skills